রবীন্দ্রনাথ ঠাকুর ও একুশ শতকের বাঙালি = Rabindranath Thakur o ekush shataker Bangali - Cakrabartī, Sumitā; Tagore, Rabindranath 1861-1941
Contributed articles on the life and works of Rabindranath Tagore, 1861-1941, Bengali author; published on the 150th birth anniversary of author.